SmJAZ8 acts as a core repressor regulating JA-induced biosynthesis of salvianolic acids and tanshinones in Salvia miltiorrhiza hairy roots. (21st December 2017) - Pei, Tianlin; Ma, Pengda; Ding, Kai; Liu, Sijia; Jia, Yanyan; Ru, Mei; Dong, Juane; Liang, Zongsuo
Abstract : SmJAZ8 regulates the biosynthesis of salvianolic acids and tanshinones simultaneously by repressing the transcription factors and biosynthetic pathway genes in Salvia miltiorrhiza hairy roots. Abstract: Jasmonates (JAs) are important plant hormones that regulate a variety of plant development and defense processes, including biosynthesis of secondary metabolites. The JASMONATE ZIM DOMAIN (JAZ) proteins act as negative regulators in the JA signaling pathways of plants. We first verified that methyl jasmonate (MeJA) enhanced the accumulation of both salvianolic acids and tanshinones in Salvia miltiorrhiza (Danshen) hairy roots by inducing the expression of their biosynthetic pathway genes. Nine JAZ genes were cloned from Danshen and their expression levels in hairy roots were all increased by treatment with MeJA. When analyzed in detail, however, SmJAZ8 showed the strongest expression in the induced hairy roots. Overexpression or RNAi of SmJAZ8 deregulated or up-regulated the yields of salvianolic acids and tanshinones in the MeJA-induced transgenic hairy roots, respectively, and transcription factors and biosynthetic pathway genes showed an expression pattern that mirrored the production of the compounds. Genetic transformation of SmJAZ8 altered the expression of other SmJAZ genes, suggesting evidence of crosstalk occurring in JAZ-regulated secondary metabolism. Furthermore, the transcriptome analysis revealed a primary–secondary metabolism balance regulated by SmJAZ8. Altogether, we propose a novel role for SmJAZ8 as a negative feedback loop controller in the JA-induced biosynthesis of salvianolic acids and tanshinones.